Manajemen Finansial Pendidikan di Indonesia (Diskursus Sistem Perpajakan pada Institusi Pendidikan) - Mesiono, Mesiono; Lubis, Rahmat Rifai (Al-Fikru: Jurnal Ilmiah, 2021)
This study aims to analyze the Education Financing System in Indonesia and its relation to the tax system. The research method used in this research is qualitative by using a library research approach (library research). Data sources consist of two namely primary and secondary. Primary data sources are several government legal regulations related to financing and the tax system in Indonesia, including law number 28 of 2007 concerning general provisions and tax procedures. Law number 36 of 2008 concerning income tax, the decision of the Director General of Taxes No. KEP-87/PJ./1995, PP. RI No.144 of 2000 concerning Types of Goods and Services that are not subject to Value Added Tax and. While secondary sources are other references in the form of books, journals, and proceedings related to the research topic. Data analysis uses content analysis, which is an analysis related to the content of the literature being researched. The results of the study indicate that one of the sources of education financing in Indonesia is tax. The use of these taxes is indeed in accordance with the legality of the government that aims for the prosperity of the people as much as possible, including in this case education services. In relation to taxpayers, not all aspects of education are subject to taxpayers, this is because educational institutions are not included in profit institutions. This treatment certainly aims to improve the quality of education in Indonesia.